2020
DOI: 10.1016/j.nicl.2020.102431
|View full text |Cite
|
Sign up to set email alerts
|

Altered dynamic effective connectivity of the default mode network in newly diagnosed drug-naïve juvenile myoclonic epilepsy

Abstract: Highlights We introduced an analysis framework to investigate the dynamic effective connectivity (DEC). The alteration of DEC in DMN was analyzed for patients with drug-naïve juvenile myoclonic epilepsy (JME). We found two distinct DEC states corresponding to strong (state 1) and week inter-influence (state 2). Patients showed state-specific EC changes that were associated with the severity of JME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…[ 71 , 72 ]. JME has been repeatedly shown to be associated with brain dysconnectivity in the DMN [ 14 , 20 ]. Qin et al [ 73 ], using synchronous EEG and fMRI methods, found that the blood oxygen level dependent (BOLD) activation areas related to high EEG network variation in JME patients were mainly located in the thalamus, cerebellum, and precuneus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 71 , 72 ]. JME has been repeatedly shown to be associated with brain dysconnectivity in the DMN [ 14 , 20 ]. Qin et al [ 73 ], using synchronous EEG and fMRI methods, found that the blood oxygen level dependent (BOLD) activation areas related to high EEG network variation in JME patients were mainly located in the thalamus, cerebellum, and precuneus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an EC analysis of JME can characterize the information flow between brain regions and therefore may provide a richer explanation of the neuropathology of JME [ 19 ]. Moreover, our previous study made the first attempt to characterize the dynamic effective connectivity (DEC) in the DMN of patients with JME, demonstrating that the DEC between brain networks is very important in JME [ 20 ]. Epilepsy is regarded as a disruption of functional networks [ 21 ], and an increasing number of studies have suggested that cerebro-cerebellar interactions are important for the induction of JME [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed generalized spike and wave discharge (GSWD)-related deactivations in the DMN, suggesting that GSWDs may interrupt the functions of the DMN [25]. Dynamic effective connectivity and independent component analyses showed complex alterations of DMN and its components in drug-naïve JME patients, indicating DMN dysfunction in the early stage of JME [26]. Interestingly, another study found significantly reduced DMN connectivity in VPA-resistant IGE patients with uncontrolled seizures, compared with responsive patients and HCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the dynamic FC, which describes the time‐varying patterns of co‐activations among brain regions, is a more efficient way for uncovering specific properties of functional communication in health and disease (Allen et al, 2014 ; Calhoun & Adali, 2016 ; Fiorenzato et al, 2019 ; F. Liu et al, 2017 ; Sun, Collinson, Suckling, & Sim, 2019 ; Tu et al, 2020 ). For patients with JME, previous studies have revealed that the dynamic FC was reduced and linked to disease severity (Wang, Berglund, Uppman, & Li, 2019 ; Zhang et al, 2018 , 2020 ). However, to our knowledge, no prior study has explored the time‐varying characteristics of SC–FC coupling in JME, and it is still unclear how anatomical connectivity constraint supports dynamic functional interaction in the rich‐club organization.…”
Section: Introductionmentioning
confidence: 95%
“…Liu et al, 2017;Sun, Collinson, Suckling, & Sim, 2019;Tu et al, 2020). For patients with JME, previous studies have revealed that the dynamic FC was reduced and linked to disease severity (Wang, Berglund, Uppman, & Li, 2019;Zhang et al, 2018Zhang et al, , 2020. However, to our knowledge, no prior study has explored the time-varying characteristics of SC-FC coupling in JME, and it is still unclear how anatomical connectivity constraint supports dynamic functional interaction in the rich-club organization.…”
Section: Introductionmentioning
confidence: 99%